Effect of Knowledge Management on Success of Customer Relationship Management in Eghtesad Novin Bank of Tehran (Global Journal of Management and Business Research, 2014)
This paper is studying on the effect of Knowledge Management on success of Customer relationship management in Eghtesad Novin Bank with using of SPSS software. Also collecting data is done through questionnaire and inferential statistics including Pearson's correlation test and Onesample t test is used for answering to the questions and research hypotheses. Finally researcher concluded that all hypotheses are confirmed and concluded that capabilities of Knowledge management, organizational variables, technology of customer relationship management, customer flow and experience of customer relationship management have positive relationship with success of customer relationship management and Knowledge Management is as main factor for determining the successful implementation of Relationship Management with Customer.
Keywords: knowledge management customer relationship management capabilities of knowledge management organizational variables technology of customer relatio